Surgical Site Infection After Autologous Cranioplasty for Decompressive Craniectomy in Traumatic Brain Injury: A Retrospective Review of Two Level 1 Trauma Centers. Issue 8 (12th November 2021) - Caruso, James P.; Griffin, Samuel; El Ahmadieh, Tarek Y.; Bedros, Nicole M.; Hoeft, Jennifer; Urquiaga, Jorge F.; Pernik, Mark N.; Hoes, Kathryn; Patel, Ankur R.; Funk, Robert H.; Davies, Matthew T.; Vance, Awais Z.; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Object: Surgical site infection (SSI) after cranioplasty can result in unnecessary morbidity. This analysis was designed to determine the risk factors of SSI after cranioplasty in patients who received a decompressive craniectomy with the autologous bone for traumatic brain injury (TBI). Methods: A retrospective review was performed at two level 1 academic trauma centers for adult patients who underwent autologous cranioplasty after prior decompressive craniectomy for TBI. Demographic and procedural variables were collected and analyzed for associations with an increased incidence of surgical site infection with two-sample independent t tests and Mann Whitney U tests, and with a Bonferroni correction applied in cases of multiple comparisons. Statistical significance was reported with a P value of < 0.05. Results: A total of 71 patients were identified. The mean interval from craniectomy to cranioplasty was 99 days (7–283), and 3 patients developed SSIs after cranioplasty (4.2%). Postoperative drain placement ( P  > 0.08) and administration of intrawound vancomycin powder ( P  = 0.99) were not predictive of infection risk. However, a trend was observed suggesting that administration of prophylactic preoperative IV vancomycin is associated with a reduced infection rate. Conclusions: The SSI rate after autologous cranioplasty in TBI patients is lower than previously reported for heterogeneous groups and indications, and the infection risk is comparable to other elective neurosurgical procedures. As such, the authors recommend attempting to preserve native skull and perform autologous cranioplasty in this population whenever possible.